TAKING LEGAL AID TO THE PEOPLE: UNLEASHING LOCAL POTENTIAL IN SOUTH AFRICA - Hennie van As (Obiter, 2022)
Two of the principal elements necessary for the establishment, maintenance and expansion of legal aid services are funding and the political will to provide the services. As far as criminal legal aid is concerned, it is clear that the will exists and the levels of funding have increased steadily over the past few years. Civil legal aid is, however, almost non-existent and it is here that the greatest need lies. South Africa being a developing country with other pressing needs, it is unrealistic to expect any drastic state-sponsored intervention any time soon. It therefore becomes imperative that innovative measures to meet the demand for basic civil legal aid, using existing resources such as members of the legal profession, students, the university law clinic and the ward committee system, should be investigated with a view to implementing at least a pilot scheme.